Design and Performance Analysis of Blades Based on the Equal–Variable Circulation Method - Liang, D.; Song, C.; Liang, S.; Wang, S.; Li, Y.; Zhou, Z. (Frontiers in Energy Research, 2021)
Aiming at improving the aerodynamic performance of the axial turbomachinery, a new type of blade is obtained based on the traditional airfoil using the equal-variable circulation method. Taking the axial flow fan as the research object, this paper designs a new type of turbomachinery by changing the design method and blade forward sweep. The aerodynamic performance of the fan is simulated and compared with the experimental data. The numerical results show that the equal circulation design method can improve the aerodynamic performance of the blade roots and the variable circulation design method can improve the aerodynamic performance of the blade tips. By adopting the design method of equal variable circulation, the total pressure of the experimental fan is increased by about 4% on the premise of keeping the efficiency unchanged. The forward-swept blades with equal-variable circulation design are also obtained by changing the center of the gravity stacking line. At low flow rate, the efficiency of the experimental fan can be increased by 7.5%, and the flow working range of the experimental fan can be expanded. Under high flow rate, it reduces the restriction of the blade on the tip air flow and slightly reduces the fluidity.